Exosome‐transmitted p120‐catenin suppresses hepatocellular carcinoma progression via STAT3 pathways. Issue 8 (17th April 2019) - Cheng, Zhangjun; Lei, Zhengqing; Yang, Pinghua; Si, Anfeng; Xiang, Daimin; Tang, Xuewu; Guo, Guangmeng; Zhou, Jiahua; Hüser, Norbert
Abstract: Hepatocellular carcinoma (HCC) is a fatal disease with increasing morbidity and poor prognosis due to surgical recurrence and metastasis. Moreover, the molecular mechanism of HCC progression remains unclear. Although the role of p120‐catenin (p120ctn) in liver cancer is well studied, the effects of secreted p120ctn transported by exosomes are less understood. Here, we show that p120ctn in exosomes secreted from liver cancer cells suppresses HCC cell proliferation and metastasis and expansion of liver cancer stem cells (CSCs). Mechanically, exosome p120ctn inhibits HCC cell progression via the STAT3 pathway, and the STAT3 inhibitor S3I‐201 abolishes the observed effects on growth, metastasis, and self‐renewal ability between exosome p120ctn‐treated HCC cells and control cells. Taken together, we propose that p120ctn‐containing exosomes derived from cancer cells inhibit the progression of liver cancer and may offer a new therapeutic strategy.